1974
DOI: 10.3758/bf03199168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of auditory stress on grooming dominance in the rat

Abstract: Two experiments examined the effects of high-intensity white noise on the subsequent monopolization of mutual grooming by dominant members of male rat pairs. Only in cases where dominants were subjected to acoustic stress in the absence of another rat did they manifest a reduction in subsequent grooming behavior. Stressed in the company of either their own submissive partners or randomly selected rats, dominants continued to monopolize mutual grooming activity. The data emphasized the relevance of the social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Several studies have reported that PTSD-like behaviors last at least 3–4 weeks after experiencing traumatic events [1, 23] and that olfactory or auditory stress alone cause cognitive and behavioral impairments in animals [18, 19]. Limited information is however available regarding the witnessing aspects of trauma and persistence of PTSD-like behaviors [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that PTSD-like behaviors last at least 3–4 weeks after experiencing traumatic events [1, 23] and that olfactory or auditory stress alone cause cognitive and behavioral impairments in animals [18, 19]. Limited information is however available regarding the witnessing aspects of trauma and persistence of PTSD-like behaviors [21].…”
Section: Introductionmentioning
confidence: 99%